Shareholder returns and financial ratios in Singapore's electrical and electronic industry - Lam, Kwan Wai (2008)
The informative value of financial ratios in explaining shareholder returns in the Singapore Electrical and Electronics industry is investigated. Correlation and regression analyses reveal that financial ratios are significant. However, investors may need to supplement financial information with non-financial performance indicators to make resource allocation decisions in the new economy.